Academic, Cognitive, and Emotional Characteristics of Incoming University Students - González Lomelí , Daniel (Consorcio de Universidades Mexicanas A.C., 2012)
In order to evaluate some of the academic and psychological indicators have new students to college in northwest Mexico, during their first academic school year is randomly selected students from 11 degrees in five regional units the institution to identify the income profile depending on the answers to a series of measurement instruments that assess variables such as the use of self-regulation strategies and career certainty. A total of 425 students majoring in Marketing and Biological Chemistry campus Caborca, Hermosillo on campus were selected races of Economics, Social Work, Linguistics, Electronics Technology, Medical and Civil Engineering; Navojoa on campus belong to the races administration and Information Systems Engineering and the Nogales campus bachelor’s degree in Organizational Communication. The results reflect the need to prepare students directly or through teachers in the development of self-regulation strategies that will lead to effective learning in combination with an orientation to their personal and academic goals, as college students and future professional discipline in which they are forming.